2021
DOI: 10.1002/hbm.25706
|View full text |Cite
|
Sign up to set email alerts
|

Cortical iron mediates age‐related decline in fluid cognition

Abstract: Brain iron dyshomeostasis disrupts various critical cellular functions, and age-related iron accumulation may contribute to deficient neurotransmission and cell death.While recent studies have linked excessive brain iron to cognitive function in the context of neurodegenerative disease, little is known regarding the role of brain iron accumulation in cognitive aging in healthy adults. Further, previous studies have focused primarily on deep gray matter regions, where the level of iron deposition is highest. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
2
5
0
Order By: Relevance
“…Our finding that only iron in the putamen increases with age is consistent with other similar studies, while some studies looking at iron deposition in cognitively healthy participants also found increases in iron with age in other regions, particularly in the caudate and hippocampus (Howard et al, 2020; Rodrigue et al, 2020; van Bergen et al, 2018; Venkatesh et al, 2021; Zachariou et al, 2021). The observed decrease in iron in the pallidum and thalamus with age is not consistent with other studies where iron in these regions either increases with age or shows no association with age (Spence et al, 2020; Venkatesh et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Our finding that only iron in the putamen increases with age is consistent with other similar studies, while some studies looking at iron deposition in cognitively healthy participants also found increases in iron with age in other regions, particularly in the caudate and hippocampus (Howard et al, 2020; Rodrigue et al, 2020; van Bergen et al, 2018; Venkatesh et al, 2021; Zachariou et al, 2021). The observed decrease in iron in the pallidum and thalamus with age is not consistent with other studies where iron in these regions either increases with age or shows no association with age (Spence et al, 2020; Venkatesh et al, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…The cognitive battery included a total of 12 computerized RT and standardized psychometric tests, with four tests administered for each of three domains of fluid cognition: perceptual-motor speed, executive function, and episodic memory (Howard et al, 2022;Madden, Jain, et al, 2020;. Each domain included one test from the cognition section of the National Institutes of Health (NIH) Toolbox (Gershon et al, 2013).…”
Section: Participantsmentioning
confidence: 99%
“…Second, quantitative imaging techniques are scarcely available in large population studies [24, 26, 31]. Quantitative imaging is particularly useful to investigate myelination and iron depositions in the brain [3335], and has been associated with cognitive performance in normal aging [13, 36]. Our neuroimaging protocol therefore not only matches the sequences of the aforementioned datasets (i.e., conventional structural T1- and T2-weighted imaging, multi-shell diffusion weighted imaging, and resting-state functional MRI), but also facilitates quantitative imaging with Magnetization Prepared 2 RApid Gradient Echoes (MP2RAGE) and Multi Echo Gradient Echo Imaging (MEGRE) sequences.…”
Section: Introductionmentioning
confidence: 99%